Simultaneous Dislocation of Radiocapitellar and Distal Radioulnar Joint. (1st October 2013) - Nishi, Tomio; Suzuki, Noriyuki; Tani, Takayuki; Aonuma, Hiroshi
Abstract : A 45-year-old male presented to the emergency room of our institution complaining of severe pain around the left elbow. While playing volleyball, he slipped down with his left arm hit between the floor and his body. He complaind of strong pain from left elbow to hand, and active motion of elbow and wrist joint was impossible. His forearm was held in supinated position. On X-ray examination, radius head was deviated to anterior lateral side, and distal end of radius was dislocated to dorsal side. Tenderness was prominent at the site of radial head and distal radioulnar joint. Surgical treatment was performed using triceps tendon strip. Good functional recovery was gained.